IMPROVING THE ORGANIZATIONAL AND ECONOMIC MECHANISM FOR INCREASING THE STRATEGIC POTENTIAL OF COMPETITIVENESS OF SERVICE SECTOR ENTERPRISES - Asenbaeva Aidaigul Edenbaevna (American Journals, 2024)
Effective management of a company's competitive potential allows you to create certain competitive advantages. Competition is an integral qualitative feature of the economic structure of society, built on the main market of economic principles, a means of self-regulation of the economic system and an element of objective international redistribution of resources between economic systems. Industries and types of activities.
Keywords: Competition, competitive potential, reserve, enterprise potential, resource, business.